MEMBEKALKAN KREATIVITAS MAHASISWA MELALUI STRATEGI PEMBELAJARAN BERBASIS STREAM MENGGUNAKAN KONTEN BIOTEKNOLOGI TRADISIONAL - Tri Wahyu Agustina; Nuryani Y. Rustaman; Riandi Riandi; Widi Purwianingsih (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2019)
Creativity is part of 21st century skills so it needs to be had by students. Therefore, the study was conducted to identify the creativity of students who take Microbiology lectures on Traditional Biotechnology content with the Science-Technology-Religion-Engineering-Arts-Mathematics (STREAM) based learning. The pre-experimental method with one-shot case study design involved 43 students from 5th semester at one of university in Bandung determined purposively. Data were collected through student worksheets, product assessment sheets and scoring of practical reports. After being collected through instruments mentioned before, data were then processed using percentage and level of creativity skills in the product of their practical reports. The results of the study show that student creativity varies for each Traditional Biotechnology content. The results of the achievement of the highest values of creativity obtained by students on indicators of elaboration thinking with emerging levels and the lowest achievement with not yet evident levels in the originality thinking. STREAM-based learning can provide student creativity skills in Traditional Biotechnology content.